Brand image on customer-based brand equity in the hotel industry in Bangladesh: tourism management and advertisement as moderators - Mohammad Wasib Latif (School of Business Innovation & Technopreneurship, 2017)
The present study focuses on exploring the key determinants of brand image for branded hotels in the context of Bangladesh. In this study, Aaker's (1996) Customer-Based Brand Equity Framework, Keller's (2003) Customer-Based Brand Equity Pyramid and Baker's (2001) Corporate Social Responsibility Model have been taken into consideration for identifying the pertinent factors affecting the image of hotel brands. Consequently a number of variables have been extracted through extensive marketing as well as branding literature review to investigate their influence on building brand image for hotels in the context of Bangladesh. The variables include brand awareness, brand association, brand superiority, brand affection, brand resonance and corporate social responsibility which are deemed to have a direct influence on brand image while tourism management and advertisement have been used as the moderators in the relationship between these six IVs and brand image. For the purpose of the study, data were collected from the customers of some selected 4 star and 5 star hotels in Bangladesh. The sample hotels were chosen from two cities of the country, which are Dhaka (capital) and Cox's Bazar sea beach city because 4 star and 5 star hotels are in operation in these two cities. From the capital city (Dhaka), six hotels have been chosen which are Radisson Water Garden Hotel Dhaka, Pan Pacific Sonargaon Dhaka Hotel, The Westin Dhaka and Dhaka Regency (5 star), Hotel Sarina (4 star) and Royal Park Residence Hotel (4 star) while four are from Cox' Bazar which are Hotel Sea Palace Limited and Seagull Hotel Cox's bazar (5 star); Long Beach Hotel Ltd. and Hotel The Cox Today (4 star).